FORMULASI KRIM ANTI-AGING DARI EKSTRAK KULIT BUAH JERUK LEMON (Citruslimon) - Silalahi, Yosy Cinthya Eriwaty; Sinaga, Eka Margaret; Thaib, Cut Masyithah (UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
Anti-aging is a preparation that is useful for preventing or slowing down the effects of aging such as wrinkles, dark spots, rough skin, and enlarged pores. Lemon peel contains flavonoids, namely hesperidin which can prevent aging and can improve skin health. This study aims to formulate anti-aging cream preparations, test the anti-aging effect, and determine the best concentration of anti-aging cream from lemon peel extract. The concentration of lemon peel extract used as a cream ingredient are: 2.5%, 5%, 7.5%, 10%. The tests carried out were homogeneity test, determination of emulsion type, pH, stability observation, skin irritation test. The test was carried out for 4 weeks. The results showed that the anti-aging cream preparations produced were homogeneous and showed an o/w type. The pH test when the cream was made was: 6-7 and after 12 weeks of storage, it was: 5-7. Anti-aging cream preparations have shown a significant increase in skin effects after 1 week, 2 weeks, 3 weeks, and 4 weeks. F5 (10% cream) provides the best anti-aging effectiveness. Lemon peel extract can be formulated into an o/a cream preparation that is able to provide anti-aging effects on the skin. Formula 5 (F5) with a concentration of 10% lemon peel extract was the most.